The Relationships of Environmental Degradation and Trade Openness in Indonesia - Oktavilia, Shanty; Firmansyah, Firmansyah (International Journal of Economics and Financial Issues, 2016)
Economic development activity lowers the quality of the environment, mainly through production with the use of natural resources excessively, and the resulting residue. The impact of the environment is intensified with the increase of international trade. This study examines how the effect of trade liberalization on environmental quality and the existence of Environmental Kuznets Curve (EKC) in Indonesia. By employing the error correction model (ECM) to annually data along 1976-2014, this study also analyses the dynamic relationship of the economic and environmental variables, in three equations, i.e. linear, quadratic and cubic. This study finds that in the long run, all equations statistically prove the effect of trade liberalization on environmental except in linear equation, and the EKC hypothesis proves on all equations. In the short run, the CO2 emission is partially influenced trade liberalization in all types of equation, and the per capita income by the quadratic equation. Keywords: Environmental Kuznets Curve (EKC), per capita income, trade liberalization JEL Clsssifications: F18, O13, Q56